Assistência estudantil como política de permanência na UFPB - Albuquerque, Larissa Cavalcanti de (2017)
This dissertation approaches the subject of student assistance as a policy of permanence at the Federal University of Paraíba. What were the difficulties and possibilities for undergraduate students to stay in the UFPB? How do university students evaluate student attendance at the UFPB? The relationship between student assistance and the right to education was defined as a research problem, whether in relation to students' access to and permanence in higher education. As a general objective, it was intended to carry out an analysis of the student assistance policy in the UFPB, from the institution of the PNAES. The historical-dialectic method was chosen, historically placing the university in Brazil in authoritarian and neoliberal contexts. The research related to student assistance dialogues with the critical perspective of education and social function of the university, using concepts such as the right to education, justice and equality, power and resistance. Specific objectives were: to analyze historically the creation and social function of the university in Brazil contextualizing the clashes with the educational reforms and the neoliberal project; to contextualize historically the policy of student assistance in Brazil and in the UFPB and the actual and materialized actions of the PNAES as a guarantee of the permanence of the students and to analyze the student perception of the policy of student assistance in the campus I of the UFPB. The methodology was based on the critical-dialectical perspective, using the qualitative approach of the case study type. The data collection phase occurred through unsystematic observation, semi-structured interview and documentary analysis. For the procedure of systematization and analysis of the data obtained in the empirical and documentary research we use content analysis. The research results confirm the need for student assistance as a factor of redistributive justice, since there are students who do not have the economic conditions to remain in the public university without the support of the State. Such a residual policy is permeated by conflicts and tensions, in the face of a disparity between the reduction of resources for policies of higher education in the neoliberal context and the needs of subalternized social segments.